PENGARUH KOMPOS TANDAN KOSONG KELAPA SAWIT TERHADAP PERTUMBUHAN dan HASIL SAWI HUMA pada TANAH ALUVIAL - Jimiando, Mantius; Zulfita, Dwi; Maulidi, Maulidi (Jurnal Sains Pertanian Equator, 2022)
The purpose of this study was to obtain the best interaction of various doses of sawdust ash and NPK fertilizer on peat soil. The research was carried out on peat land, Jungle Jaya hamlet, Sungai Duri village, Sungai Raya sub-district, Bengkayang Regency, West Kalimantan. The research design used was a randomized block design with 2 factors and 3 treatment levels. Powder ash factor consisting of a1=1.8 kg/plot, a2=2.7 kg/plot, a3=3.5 kg/plot and NPK fertilizer factor consisting of m1=22.25 gr/plot, m2= 37.50 gr/plot, m3=45.00 gr/plot. Planting is done by placing the seeds in each planting hole with a total of two seeds with a spacing of 25 cm x 25 cm per planting hole. Variable observations were made on plant height, plant dry weight, number of pods, weight of pods, number of filled pods, and number of seeds. The results showed that the application of sawdust ash and NPK fertilizer doses of 2.7 kg/plot and 37.50 g/plot had a significant effect on all observed variables.Keywords: compost empty bunches of oil palm, mustard huma, alluvial soil.